Analisis Kemampuan Berbicara di Depan Umum Mahasiswa STAKat Negeri Pontianak sebagai Calon Guru Agama Katolik - Bunga, Jimiana (Jurnal Pendidikan Bahasa, 2025)
Public speaking is an essential skill for prospective Catholic religious teachers, as they serve as communicators of faith in both educational and pastoral contexts. This study aims to analyze the public speaking abilities of first-semester students at STAKat Negeri Pontianak and identify the challenges they face. A qualitative method was employed, with data collected through interviews and direct observation of students in the 2024 Catholic Religious Education program. The findings reveal that while students demonstrate adequate articulation and voice intonation, they still struggle with content mastery, body language, eye contact, and emotional control when speaking in public. These challenges negatively affect the overall effectiveness of their communication. Therefore, continuous training and guidance are needed to enhance students’ readiness to become confident, communicative, and inspiring religious educators.